MicroRNAs as Possible Biomarkers for Diagnosis and Therapy of Alzheimer’s Disease by Regulating the Abnormal Expression of Genes Related to Tau - Tang Mengzhu (BIO Web of Conferences, 2023)
Alzheimer’s disease (AD), the most common dementia with the symptom of deterioration of memory and cognitive functions, becomes one of the prevalent threats globally. Tau hyperphosphorylation is one of major risk factors of AD. At present, there is no effective treatment or quick diagnostic methods for the pre-clinical stage of this disease. MicroRNAs (miRNAs) are small (20-25bp) non-coding, double stranded RNA molecule. They mainly regulate gene expression during the post-transcription by binding to the 3-’UTR of the mRNA then stop translation. Unlike other biomarkers using for Alzheimer’s disease, miRNAs are stable and widely found in body fluids such as serum, tissues, and Cerebrospinal fluid (CSF) and one miRNA can regulate multiple genes. As a result, they are potentially used as diagnosis or therapeutic biomarkers for many diseases including Alzheimer’s disease. Currently, this field that using miRNAs as biomarkers for diagnosis and treatment has been rapidly developed. To examine the mechanism and function of miRNAs and potential in AD, this review summarizes current diagnostic and therapeutic techniques and comparing several microRNAs that especially regulating tau toxicity as practicable diagnostic biomarkers and treatment agents. It is likely to detect different stages of Alzheimer’s disease and reduce Tau hyperphosphorylation if this field of miRNA as biomarkers carries forward.